Literature Study: Elementary School Mathematics Learning with Islamic Integration - Hasibuan, Vira Amelia Pratiwi; Mariana, Neni; Ekawati, Rooselyna (International Journal of Emerging Research and Review, 2024)
Objective: The way math thinks is systematic through sequence and systematic By learning math, we can solve problems systematically. So that problems can be easily solved. The relationship with Islam, as Muslims are sourced from the Qur'an and hadiths, the problems faced can be solved with mathematics but are still based on the learning and manners that have been taught in religion. Method: This study uses SLR (Systematic et al.) research, where the data source is obtained from existing articles published by OJS (Online et al.). Articles obtained through Google Scholar and DOAJ searches were then organized into tables. Result: This research shows that obtained regarding the role of integration of Islamic values in mathematics learning are: 1) able to improve students' positive character, especially religious attitudes; 2) increase students' interest and motivation to learn mathematics; 3) improve students' ability to solve math problems and 4) able to improve student learning outcomes and able to improve student learning outcomes. Novelty: Based on these findings, it is expected that educators will try to be able to integrate Islamic values into mathematics learning.